Forward Contamination of Ocean Worlds: A Stakeholder Conversation. (May 2019) - Sherwood, Brent; Ponce, Adrian; Waltemathe, Michael
Abstract: A fundamental requirement for space missions designed to touch "potential habitats" is the single number 10 −4, the allowable probability of a single Earth organism contaminating the potential habitat. Many aspects of a mission that affect its complexity and cost—hardware design and manufacture, assembly and test, and mission operations—are driven by this value; therefore, it is important, on the threshold of an era of exploring ocean worlds, to have confidence in it. Yet, despite its long pedigree and occasional reviews, we find that the current requirement lacks programmatically defensible justification. At issue are three weaknesses: (1) microbial biology, in particular the science of extremophiles, is a rapidly changing field; (2) forward contamination (FC) is both a scientific and an ethical issue, yet no ethics-based conversation is apparent within policy-setting circles; and (3) because of these 2 factors, policy-setting cannot be static. We review the history of the requirement, how the evolving understanding of biology could drive it up or down, how the FC hazard relates to risk-management practice and to the ethics profession, and how a contemporary stakeholder conversation could adapt lessons already learned by other fields.